(3GdYUGs - (3GSGeI Hf efbP , GSGeI Hf eQTO Hf Ydj Hf ebdO Hf fUQ Hf efbP GdcfGfj GdcdHj, CHh GdeXaQ,J (B584 (3g` s
(3ChdgG (B:s
(3aEf GdfaS JQJGM deG SeYJ, hJdM aj GdWdH EPG oefYJ, hcGf GdhGdO GdSYjO eLOGdOjf CHhSdGeI eQTO Hf Ydj s
(3BNQgG (B:s
(3bGd Gdehdi eDjO GdOhdI eDda gPG GdcJGH CWGd Gddg HbGAg gPG BNQ eG bdJg hLeYJg hCdaJg hQUaJg aj PcQ GdYUG s
(3eMahXI HGdecJHI GdhWfjI aj ChHSGdG GdShjO hHChd gPg GdfSNI Jedc ddSjO LeGd GdOjf Hf GdeXaQ aj Gdjef eDQN (B1068(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B37 s
Keywords: (3GdCOHs